2001
DOI: 10.1021/la001309z
|View full text |Cite
|
Sign up to set email alerts
|

Studies of N-Dodecyllactobionamide, Maltose 6‘-O-Dodecanoate, and Octyl-β-glucoside with Surface Tension, Surface Force, and Wetting Techniques

Abstract: Three different types of sugar surfactants, octyl-β-glucoside, maltose 6′-O-dodecanoate, and Ndodecyllactobionamide have been investigated to examine the effect of the structure of the sugar headgroup on the adsorption to liquid/vapor and solid/liquid interfaces using a number of techniques (surface tension, surface force apparatus, MASIF, and wetting). It was found that all the surfactants form monolayers when adsorbed to a hydrophobic interface at high concentrations. Increased headgroup flexibility leads to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 68 publications
(88 reference statements)
1
39
1
Order By: Relevance
“…CMC values obtained from the break-points of the surface tension isotherms (estimated as the intersection of lines fitted to the descending and flat portions of the curves) were in good agreement with those obtained by the dye-inclusion method (Table I). The minimum surface tension, γ min , was in the range 47-53 mN/m, which is remarkably high compared to many sugar-based surfactants (Augé and LubinGermain, 2000;Ericsson et al, 2004;Ferrer et al, 2002;Garofalakis et al, 2000;Kjellin et al, 2001;Persson et al, 2000;Söderberg et al, 1995;Waltermo et al, 1996). An anomalously high γ min value can result when the Krafft point of the surfactant is passed at high concentration, which effectively results in the precipitation of the surfactant from solution.…”
Section: Concentration (G/l)mentioning
confidence: 88%
See 2 more Smart Citations
“…CMC values obtained from the break-points of the surface tension isotherms (estimated as the intersection of lines fitted to the descending and flat portions of the curves) were in good agreement with those obtained by the dye-inclusion method (Table I). The minimum surface tension, γ min , was in the range 47-53 mN/m, which is remarkably high compared to many sugar-based surfactants (Augé and LubinGermain, 2000;Ericsson et al, 2004;Ferrer et al, 2002;Garofalakis et al, 2000;Kjellin et al, 2001;Persson et al, 2000;Söderberg et al, 1995;Waltermo et al, 1996). An anomalously high γ min value can result when the Krafft point of the surfactant is passed at high concentration, which effectively results in the precipitation of the surfactant from solution.…”
Section: Concentration (G/l)mentioning
confidence: 88%
“…where N A is Avogadro's number Garofalakis et al, 2000;Kjellin et al, 2001;Söderberg et al, 1995). The standard free energy of micellization was calculated from CMCs determined by the dye-inclusion method using the relationship (Augé and Lubin-Germain, 2000;Eastoe et al, 1996) ∆G mic = RT ln(CMC/55.5)…”
Section: Analytical Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…The maximum solubilizing capacity was estimated from the intersection of the two lines drawn at the low and high concentrations. Figure 4 shows the concentration of octanoic acid solubilized into the micelle at the various surfactant (monolauroyl disaccharide) concentrations for the four monolauroyl di- (Ferrer et al, 2002) and 0.33 mmol/L at 22℃ (Kjellin et al, 2001), and those of the monolauroyl sucrose were 0.45 mmol/L at 20℃ (Söderberg et al, 1995), 0.25 mmol/L at 25℃ (Ferrer et al, 2002), and 0.21 mmol/L at 32℃ (Garofalakis et al, 2000). The CMC values of the monolauroyl disaccharides synthesized in this study were almost the same as the reported ones.…”
Section: Resultsmentioning
confidence: 99%
“…Fatty acid esters of other di-, monoand trisaccharides have also been shown to be surface active (Söderberg et al, 1995;Garofalakis et al, 2000;Kjellin et al, 2001;Douglas and Tao, 2002;Ferrer et al, 2002;Zhang et al, 2003;Chen et al, 2005;Chen et al, 2007;Piao et al, 2007;Sun et al, 2009). Recently, enzymatic synthesis in organic solvents has attracted attention as an alternative to conventional chemical synthesis of esters (Carrea and Riva, 2000).…”
Section: Introductionmentioning
confidence: 99%